Qat Chewing and risk of potentially malignant and malignant oral disorders: A systematic review - El-Zaemey, Sonia; Schüz, J.; Leon, M. (2015)
© 2015, NIOC Health Organization. All right resurved. Background: Qat(also known as Khat, Kat andMiraa) is a green-leaved plant (Catha edulis). It is a shrub indigenous to Yemen and certain parts of eastern Africa. Chewing the leaves, which have sympathomimetic and euphoric effects, has been documented in many countries and increased with worldwide migration. The effect of long-term chewing Qaton the oral cavity is unknown. Objective:A systematic review was performed to identify any associations between Qat chewing and the occurrence of potentially malignant and malignant oral disorders. Methods:Medline and the Web of Science were searched for articles published before May 2014 without limits with regard to publication date and language. Results:From a total of 890 papers identified, 17 English papers reported potentially malignant or malignant oral disorders and Qat chewing. One additional paper in Arabic language was identified from reviewing the list of references of eligible papers. It was found that exposure to Qatmay be associated with potentially malignant and malignant oral disorders, but methodological issues, such as inadequate study design, sample size, selection of study subjects, clinical evaluations of outcome and limited adjustment for confounders, limit the strength of the evidence base in this area. Conclusion:The association between Qat chewing and potentially malignant and malignant oral disorders remains debatable and requires further investigations.